2022
DOI: 10.1002/tesq.3143
|View full text |Cite
|
Sign up to set email alerts
|

Google Translate and Biliterate Composing: Second‐Graders' Use of Digital Translation Tools to Support Bilingual Writing

Abstract: Research is needed exploring how teachers and students in Englishmedium schools transform classrooms to welcome and value bilingualism and biliteracy. This article draws on social literacies and placed resources perspectives to explore how one classroom of second-grade students used Google Translate as a tool to support their biliterate composing. Constant comparative analyses revealed three patterns related to students' use of this tool. Students used Google Translate to support their inclusion of bilingual t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…It served as an essential survival tool for pupils to communicate with their teachers and peers [1]. Many studies also indicated that machine translation acted as a language learning resource [35,38]. It was instrumental for students in gaining knowledge, including vocabulary, grammar, pronunciation, and spelling [4,27,33,38].…”
Section: Students' Attitudesmentioning
confidence: 99%
See 4 more Smart Citations
“…It served as an essential survival tool for pupils to communicate with their teachers and peers [1]. Many studies also indicated that machine translation acted as a language learning resource [35,38]. It was instrumental for students in gaining knowledge, including vocabulary, grammar, pronunciation, and spelling [4,27,33,38].…”
Section: Students' Attitudesmentioning
confidence: 99%
“…These resulted in little trust in machine translation. On the other hand, students may become overdependent on the machine output and accept it without postediting [33,35], suggesting a lack of critical analytic skills [40]. In this case, they would develop bad habits and become less motivated and enthusiastic to learn [39].…”
Section: Students' Attitudesmentioning
confidence: 99%
See 3 more Smart Citations